A STRATEGIC LINGUOCULTUROLOGICAL MODEL FOR TEACHING ONOMASTIC UNITS IN ENGLISH AND UZBEK LANGUAGE EDUCATION - Mamatkulova Bakhtijon Ravshanovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article develops a strategic linguoculturological model for teaching onomastic units in English and Uzbek language education. It argues that proper names function as culturally embedded linguistic units that reflect national identity, historical memory, and social values. The study integrates strategic teaching principles with linguoculturological analysis to design an effective instructional model. The proposed model combines comparative, cognitive, and communicative strategies to facilitate deeper comprehension of onomastic meanings. The findings demonstrate that a strategically structured approach to onomastics significantly enhances learners’ intercultural communicative competence, analytical thinking, and pragmatic language use.